Design of Control System for Concrete Machine based on PLC and HMI - Abdeladim Moftah; Salwa I. Almoshity; Abdullah Majeed; Ahmed Ghafeer (African Journal of Advanced Pure and Applied Sciences, 2024)
Concrete is the backbone of construction and infrastructures. It is widely used in industrial plants, civil infrastructures, wastewater treatment plants, and it is used among many other fields. Concrete is a homogeneous mixture of cement, sand, water and coarse aggregates. Concrete mixers are the machines responsible for mixing the four components in different proportions to obtain various classes of concrete. They ensure the consistency of the mixture and guarantee that the desired specifications are met in a steady and reliable process operation. The objective of the paper is to design and implement an automated concrete mixer that can produce different concrete types depending on the operator settings. The paper uses Programmable Logic Controller (PLC), Human Interface Machine (HMI), measuring sensors, actuators and control switches. The paper also uses software programs and logics that allow the user to program and control the hardware parts. The use of these equipment and tools ensures that the user can achieve a completely automated operation that is free of human labor and to reach a high degree of accuracy.